Pengaruh Adverse Selection Dan Negative Framing Terhadap Eskalasi Komitmen Dalam Pengambilan Keputusan Investasi - Siti Zakiyah Hayati Nasution; Rindah Febriana Suryawati (Jurnal Manajemen dan Organisasi, 2019)
Escalation of commitment behavior in investment decision making is an ineffective action by persisting on a project that indicates failure. This study aims to examine whether or not an adverse selection and negative framing effect on the tendency of escalation of commitment. This experimental research uses a 2 x 2 factorial design with an instruments of "PT Kue Hebat" case. Participants were Bachelor Degree of Management students who enrolled in Financial Management subject, as substitute for managers whom are chosen by random assignment technique as much as 50 participants. This study uses two ways ANOVA analysis techniques. The results of the study prove that the project manager will show a tendency to escalate commitment by continuing unfavorable projects in adverse selection conditions or in negative framing conditions.